2008
DOI: 10.1038/nm.1864
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib-induced enzyme-targeted radiation therapy in herpesvirus-associated tumors

Abstract: We investigated the possibility of using a pharmacologic agent to modulate viral gene expression in order to target radiotherapy to tumor tissue. In a murine xenograft model, we had previously shown targeting of [125I]2'-fluoro-2'-deoxy-beta-D-5-iodouracilarabinofuranoside ([125I]FIAU) to tumors engineered to express the Epstein-Barr virus (EBV)-thymidine kinase (TK). Here we extend those results to targeting of a therapeutic radiopharmaceutical [131I]FIAU to slow or stop tumor growth or to achieve tumor regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 23 publications
1
98
0
Order By: Relevance
“…Evaluation of additional cytotoxic approaches specifically targeting cells expressing KSHV lytic genes appears warranted in KSHV-MCD. 51 As our understanding of this rare disease continues to improve, durable remissions for the majority of HIV-infected patients with KSHV-MCD obtained through the use of targeted therapy appear to be an attainable goal.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of additional cytotoxic approaches specifically targeting cells expressing KSHV lytic genes appears warranted in KSHV-MCD. 51 As our understanding of this rare disease continues to improve, durable remissions for the majority of HIV-infected patients with KSHV-MCD obtained through the use of targeted therapy appear to be an attainable goal.…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib was reported to induce EBV lytic cycle in EBV-positive Burkitt lymphoma and gastric carcinoma cells (25). Induction of EBV lytic cycle by bortezomib could activate the radioisotope [ 125 I]2 0 -fluoro-2 0 -deoxy-b-D-5-iodouracil-arabinofuranoside to selectively suppress the growth of Burkitt lymphoma xenografts in severe combined immunodeficient (SCID) mice (25). Our laboratory has previously shown that SAHA could significantly induce viral lytic cycle in EBV-positive gastric carcinoma and NPC cells and mediates enhanced apoptosis (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic approaches require further research on virus-host interactions in EBV-associated neoplasms (16). Since viral replication is inhibited by promoter methylation in EBV DNA, demethylating agents, such as 5-azacytidine, may induce lytic infection by EBV, leading to lysis of infected cells (17).…”
Section: Discussionmentioning
confidence: 99%